2019
DOI: 10.1002/dys.1630
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Chinese EFL teachers' knowledge and beliefs relating to the teaching of English reading in public primary schools in China

Abstract: The present study explored knowledge and beliefs about reading instruction of Chinese teachers teaching English as a foreign language (EFL). Theoretical Orientation to Reading Profile and the Survey of Basic Language Constructs Related to Literacy Acquisition were administered to 262 EFL teachers in the south‐eastern part of China. Additionally, three teachers were interviewed, and their instructional practices were observed. The results showed that there was no correlation between teachers' self‐efficacy beli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 45 publications
3
10
0
Order By: Relevance
“…However, none of the participants' views about good reading instruction reflect the need to develop students' metacognitive reading skills. This finding is in line with Chinese EFL teachers in a study conducted by Luo et al (2019) in which teachers are reported to find difficulties in using metalanguage in their reading instruction. The teachers are aware that reading involves the students' activation of schemata in the cognitive process (Barnawi, 2013), although they have not been able to extend their understanding to help students make efficient use of the cognitive process.…”
Section: Think Successful Reading Instruction Enables Students To Understand the Text To Answer The Questions Based On The Pre-designed Isupporting
confidence: 88%
See 3 more Smart Citations
“…However, none of the participants' views about good reading instruction reflect the need to develop students' metacognitive reading skills. This finding is in line with Chinese EFL teachers in a study conducted by Luo et al (2019) in which teachers are reported to find difficulties in using metalanguage in their reading instruction. The teachers are aware that reading involves the students' activation of schemata in the cognitive process (Barnawi, 2013), although they have not been able to extend their understanding to help students make efficient use of the cognitive process.…”
Section: Think Successful Reading Instruction Enables Students To Understand the Text To Answer The Questions Based On The Pre-designed Isupporting
confidence: 88%
“…Emphasizing the "means-oriented actions", teachers in their study reported particular classroom procedures-reading, translation, rehearsing, and testing the vocabulary-which often downplays students' agency in the classroom reading activities (Bakken & Lund, 2018, p. 82). Moreover, these routines are legitimized by the testing culture of ELT in many countries, such as Norway and China (Bakken & Lund, 2018;Luo et al, 2019). In the context of the present study, the teachers' belief in prioritizing teaching reading to the test can be understood within the heavy examination orientation characterizing ELT in Indonesia (Sukyadi & Mardiani, 2011).…”
Section: Think Successful Reading Instruction Enables Students To Understand the Text To Answer The Questions Based On The Pre-designed Imentioning
confidence: 77%
See 2 more Smart Citations
“…Moreover, English newspapers and periodicals cover a wide range of contents, which can enable students to obtain relevant knowledge and information in various fields in the process of reading, help students understand the cultural background of different countries and regions, and enable students to more objectively understand the traditional culture and modern civilization of other countries and peoples [ 6 ]. On the other hand, to a certain extent, it can also deepen students' recognition of their own culture, which is conducive to the formation of students' correct outlook on life, and values, and lay a solid foundation for their future study, work, and life [ 7 ]. The significance and function of English newspaper reading are shown in Figure 1 .…”
Section: Introductionmentioning
confidence: 99%